2023
DOI: 10.3390/nu15020463
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Protein Restriction in Rats Alters Postnatal Growth and Brain Lipid Sensing in Female Offspring

Abstract: Perinatal nutrition is a key player in the susceptibility to developing metabolic diseases in adulthood, leading to the concept of “metabolic programming”. The aim of this study was to assess the impact of maternal protein restriction during gestation and lactation on glucose homeostasis and eating behaviour in female offspring. Pregnant rats were fed a normal or protein-restricted (PR) diet and followed throughout gestation and lactation. Body weight, glucose homeostasis, and eating behaviour were evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…These studies are consistent with the authors' in the context of the overall goal, but do not agree on the results, since V.S. Moullé et al (2023) fed the study group a limited level of protein, and the authors of the presented studies did not bring the level of protein to a deficiency in any of the groups, but its origin was different.…”
Section: Resultssupporting
confidence: 45%
See 1 more Smart Citation
“…These studies are consistent with the authors' in the context of the overall goal, but do not agree on the results, since V.S. Moullé et al (2023) fed the study group a limited level of protein, and the authors of the presented studies did not bring the level of protein to a deficiency in any of the groups, but its origin was different.…”
Section: Resultssupporting
confidence: 45%
“…V.S. Moullé et al (2023) experimentally demonstrated that groups with lower protein content during pregnancy and lactation were characterized by lower weight parameters compared to groups with a balanced diet. These studies are consistent with the authors' in the context of the overall goal, but do not agree on the results, since V.S.…”
Section: Resultsmentioning
confidence: 99%
“…Gestational protein restriction disrupts this process of neurogenesis and cell fate determination ( 75 , 76 ), leading to fewer NPY neurons and attenuated projections from the arcuate nucleus to the paraventricular nucleus ( 77 , 78 , 79 ). This is manifested in hyperinsulinemia, increased body weight, hyperleptinemia, and altered leptin responsiveness, which are hallmarks of metabolic syndrome, in adult offspring ( 78 , 80 , 81 ). Another study found that altered expression of genes encoding NPY, POMC, and leptin receptor isoforms was evident in the protein-deprived fetal brain as early as G12 ( 82 ).…”
Section: Neuroanatomical and Behavioral Consequencesmentioning
confidence: 99%